Tropism and molecular pathogenesis of canine distemper virus. (2019)
Canine distemper virus (CDV), currently termed Canine morbillivirus, is an extremely contagious disease that affects dogs. It is identified as a multiple cell tropism pathogen, and its host range includes a vast array of species. As a member of Mononegavirales, CDV has a negative, single-stranded RNA genome, which encodes eight proteins.